2019
DOI: 10.26710/jbsee.v5i2.811
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education, School Culture and Organizational Commitment among High Schools in South Sumatra Indonesia

Abstract: The role of entrepreneurship in the education sector is required in order to achieve innovative institutes through various productive programs. In order to pursue a more developed country, Entrepreneurship Education (EE) is needed to create innovative characteristics and entrepreneurial talents whereby economic growth and employment are stimulated. Unfortunately, the entrepreneurship curriculum was a few to be implemented in South Sumatra. Likewise, this issue caused a lower school culture and also the commitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, education practitioners should improve under the circumstances and schools need in Indonesia. Usman (2006)suggested that school-based management will play a good role when considering the following principles: (1) the principal and all school members must make a firm commitment to the implementation of school-based management, (2) all school residents should implement School-based management to prepare them physically and psychologically; (3) Effective education is education involving all parties; (4) School is the most crucial institution in education management; (5) Make all school decisions to truly understand education; (6) Teachers should be conscious of assisting the principal making educational plan decisions and curriculums; (7) The school should be given the most excellent autonomy to be independent in decision-making and financial management; (8) If the school's interests Stakeholders participate, and the change will last longer (Marchalina, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, education practitioners should improve under the circumstances and schools need in Indonesia. Usman (2006)suggested that school-based management will play a good role when considering the following principles: (1) the principal and all school members must make a firm commitment to the implementation of school-based management, (2) all school residents should implement School-based management to prepare them physically and psychologically; (3) Effective education is education involving all parties; (4) School is the most crucial institution in education management; (5) Make all school decisions to truly understand education; (6) Teachers should be conscious of assisting the principal making educational plan decisions and curriculums; (7) The school should be given the most excellent autonomy to be independent in decision-making and financial management; (8) If the school's interests Stakeholders participate, and the change will last longer (Marchalina, 2019).…”
Section: Introductionmentioning
confidence: 99%